Risk aversion, level and incentive effects: a laboratorial experiment with ufc students - Soares, Ricardo Brito; Simôes, Patrícia; Jorge Neto, Paulo de Melo (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This paper makes an empirical study about decision making under uncertainty among students of the Federal University of Ceará. In order to measure individual risk preferences, an elicitation technique called the Multiple Price Lists is used. Such a methodology was popularized by Holt and Laury (2002) and makes use of a list of paired lotteries, structured in such a way that the number of safe choices of the individual can be used to estimate his or her degree of risk aversion. As a result, the level of risk aversion found is higher than predicted by the theory and the hypothesis of the value scale effect as well as that of the monetary incentive effect are validated by the experiment. Thus, this work shows that there is a tendency to underestimate the willingness of individuals to take risks in hypothetical laboratory experiments, with the possibility of economic losses.